“Get on with it. Cope.” The compassion-experience during COVID-19 in UK universities - Denney, Fiona (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic caused major disruption to all sectors including higher education during the years of 2020 and 2021, thus providing a window into how different types of suffering can combine and the role of compassion in alleviating pain. Higher education within the United Kingdom provides a case example in this study, but the lessons about compassion are transferable to other contexts, particularly those in the neoliberal public sector. The impact of the pandemic period on teaching in universities has been well documented but there has been far less written about the wider experiences of staff who worked through this period, their suffering and the extent of compassion within their work lives. Methods 29 interviews were conducted and individuals were invited to talk through the story of their pandemic experiences from March 2020 to the interview date of December 2021. Storytelling is a common method in organization studies and, although research into compassion in organizations is nascent, this method has been used in other studies. Results and discussion Previous research has examined organizational compassion in short periods of crisis and this study therefore provides a contrasting perspective on how compassion shifts over a longer period of suffering. A distinction is drawn in this study for the first time between “formalized” compassion processes in the organization which structurally prioritized compassion for students over that of staff, and “informal” compassion shown between staff to each other and between students and staff. The more that formalized compassion was evident, the less apparent it was in interpersonal interactions due to staff wellbeing being compromised and a systemic failure to recognize the dependence of student compassion on the wellbeing of staff. The findings therefore lead to theorizing that although neoliberal universities are perceived as being full of organizational neglect, compassion was structurally embedded for students but at the expense of staff.